Simple and robust polymer-based sensor for rapid cancer detection using serum. Issue 76 (6th September 2019) - Le, Ngoc D. B.; Singla, Arvind K.; Geng, Yingying; Han, Jinsong; Seehafer, Kai; Prakash, Gyan; Moyano, Daniel F.; Downey, Charlene M.; Monument, Michael J.; Itani, Doha; Bunz, Uwe H. F.; Jirik, Frank R.; et al.
Abstract : Rapid detection of cancer using a simple FRET-based polymer sensor. Abstract : We report a polymer-based sensor that rapidly detects cancer based on changes in serum protein levels. Using three ratiometric fluorescence outputs, this simple system identifies early stage and metastatic lung cancer with a high level of accuracy exceeding many biomarker-based assays, making it an attractive strategy for point-of-care testing.